Functional diversity of the Barents Sea fish community - Wiedmann, Magnus Aune; Aschan, Michaela; Certain, Gregoire; Dolgov, Andrey V.; Greenacre, Michael; Johannesen, Edda; Planque, Benjamin; Primicerio, Raul (Marine Ecology Progress Series, 2014)
This paper provides the first assessment of the functional diversity (FD) of the Barents Sea fish community. FD is recognized as an important driver of ecosystem functions and, thus, governs the adaptability of ecosystems in the face of disturbance. We integrate ecosystem survey data with an extensive trait matrix and show that fish FD displayed large spatial variation. The study period (2004 to 2009) was characterized by increasing water temperatures and decreasing ice coverage. FD remained stable between years in some areas but showed substantial variation in other areas. For instance, FD was consistently high in the central-west Barents Sea because of the high richness of functionally homogeneous species, whereas it varied strongly in northern areas through time. Such patterns of strong variation were probably driven by the strong warming trend registered in the study period. The species found in the eastern Barents Sea were more functionally distinct than those found in the west. Even though this pattern indicates that assemblages in the eastern areas display high adaptability relative to the number of species present, species loss in these areas will have a higher impact on the FD. Our findings show that FD gives more information about fish community structure and functioning than traditional biodiversity measures, and we suggest that such trait-based methods may constitute useful tools for future monitoring and management of marine fish communities.